Bridging the Quality Gap: Analyzing NAAC Accreditation and IQAC’s Role in Higher Education Transformation - Davda Parita Yatish; Darshana Vithalani (International Journal of Education Sciences, 2025)
The role of the National Assessment and Accreditation Council (NAAC) and Internal Quality Assurance Cells (IQAC) in ensuring quality standards in higher education institutions (HEIs) in India has been a subject of extensive research. This review synthesizes existing literature to assess the impact of NAAC accreditation on institutional quality enhancement, transparency, curriculum flexibility, and overall governance. A comparative approach highlights the role of IQAC in implementing continuous quality improvement mechanisms. While significant improvements have been observed in curriculum design, faculty development, and institutional accountability, challenges such as limited funding, uneven regional implementation, and resistance to change persist. This paper identifies research gaps and proposes a future research agenda to bridge theoretical and practical concerns in accreditation frameworks.
Keywords: IQAC; Institutional Performance; NAAC Accreditation; continuous improvement; higher education; quality assurance